2020
DOI: 10.3390/nu12103195
|View full text |Cite
|
Sign up to set email alerts
|

The Extract of Arctium lappa L. Fruit (Arctii Fructus) Improves Cancer-Induced Cachexia by Inhibiting Weight Loss of Skeletal Muscle and Adipose Tissue

Abstract: Background: Cachexia induced by cancer is a systemic wasting syndrome and it accompanies continuous body weight loss with the exhaustion of skeletal muscle and adipose tissue. Cancer cachexia is not only a problem in itself, but it also reduces the effectiveness of treatments and deteriorates quality of life. However, effective treatments have not been found yet. Although Arctii Fructus (AF) has been studied about several pharmacological effects, there were no reports on its use in cancer cachexia. Methods: To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 58 publications
1
8
1
Order By: Relevance
“…However, further investigation from this work suggests that the p38α-specific inhibitor VCP979 has a more prominent effect on inhibiting adipocyte differentiation and ameliorating CAC. Importantly, our results are consistent with those reported by Felipe Henriques et al [ 52 ] and Han et al [ 53 ], all supporting that the suppression of adipose tissue browning induced by CAC can increase survival and p38α could serve as a novel druggable target to combat metabolic diseases such as cachexia.…”
Section: Discussionsupporting
confidence: 93%
“…However, further investigation from this work suggests that the p38α-specific inhibitor VCP979 has a more prominent effect on inhibiting adipocyte differentiation and ameliorating CAC. Importantly, our results are consistent with those reported by Felipe Henriques et al [ 52 ] and Han et al [ 53 ], all supporting that the suppression of adipose tissue browning induced by CAC can increase survival and p38α could serve as a novel druggable target to combat metabolic diseases such as cachexia.…”
Section: Discussionsupporting
confidence: 93%
“…In our study, this readout parameter was uninformative for differentiating between baseline data and data derived from tumor-bearing mice. This is inconsistent with the widely published concept that severe weight loss can be observed in some animal models during tumor growth [ 20 , 33 ]. However, several other publications also describe that the total body weight was not reduced in tumor-bearing mice [ 34 , 35 , 36 , 37 , 38 ].…”
Section: Discussioncontrasting
confidence: 82%
“…Some authors also mention that the weight of the tumor itself and intraperitoneal effusion may mask the body weight loss [ 39 ]. Another study on a mouse xenograft model demonstrated that the size of subcutaneous tumors increased the total body weight of tumor-bearing mice [ 33 ]. However, these studies did not compare the adjusted body weight to other readout parameters for distress and did not address the issue if adjusted body weight change has the diagnostic ability to differentiate between mice with and without a tumor.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, polysaccharides obtained from extracts of A. lappa regulated lipid metabolism in animal models for type 1 and 2 diabetes [79,80] . Different other properties have also been reported as effective in the treatment of several conditions including, acne, [130] anti‐aging, [44,131] antiobesity, [89] skin whitening agent, [19] anti‐constipation and intestinal flora regulation, [83] neuroprotective effect, [13,82] hepatoprotective, [7,78,86] anti‐tuberculosis, [61] anti‐ulcer, [24,56] and cachexia induced by cancer [132] …”
Section: A Lappa Biological Activitiesmentioning
confidence: 99%